How physician and community pharmacist perceptions of the community pharmacist role in Australian primary care influence the quality of collaborative chronic disease management - Rieck, A.; Pettigrew, Simone (Radcliffe Medical Press Ltd., 2013)
Background Community pharmacists (CPs) have been changing their role to focus on patient-centred services to improve the quality of chronic disease management (CDM) in primary care. However, CPs have not been readily included in collaborativeCDM with other primary care professionals such as physicians. There is little understanding of the CP role change and whether it affects the utilisation of CPs in primary care collaborative CDM.Aim To explore physician and CP perceptions of the CP’s role in Australian primary care and how these perceptions may influence the quality of physician/CP CDM programmes.Methods Data were collected from physicians and CPs using semi-structured interviews. A qualitative methodology utilising thematic analysis was employedduring data analysis. Qualitative methodology trustworthiness techniques, negative case analysis and member checking were utilised to substantiate the resultant themes.Results A total of 22 physicians and 22 CPs were interviewed. Strong themes emerged regarding the participant perceptions of the CP’s CDM role in primary care. The majority of interviewed physicians perceived that CPs did not have the appropriate CDM knowledge to complement physician knowledge to provide improved CDM compared with what they could provide on their own. Most ofthe interviewed CPs expressed a willingness and capability to undertake CDM; however, they were struggling to provide sustainable CDM in the business setting within which they function in the primary care environment.Conclusions Role theory was selected as it provided the optimum explanation of the resultant themes. First, physician lack of confidence in the appropriateness of CP CDM knowledge causes physicians to be confused about the role CPs wouldundertake in a collaborative CDM that would benefit the physicians and their patients. Thus, by increasing physician awareness of CP CDM knowledge,physicians may see CPs as suitable CDM collaborators. Second, CPs are experiencing role conflict and stress in trying to change their role.Strengthening the service business model may reduce these CP role issues and allow CPs to reach their full potential in CDM and improve the quality ofcollaborative CDM in Australian primary care.